THE EFFECT OF MUROTTAL AL-QUR'AN THERAPY ON CHANGES IN ANXIETY IN THE ELDERLY WITH HYPERTENSION IN THE KALIKOTES HEALTH CENTER WORK AREA - Agustina, Lusinta; Suryani, Emy; Aurellia, Tita (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Hypertension has become a global health problem as well as one of the leading causes of death that occurred suddenly so often called "the silent killer", causing increased morbidity including in Indonesia. The prevalence of hypertension in Indonesia indicates a measurement of 34.1% of the population, with the majority of those suffering from such high blood pressure being in the elderly. This real high blood pressure can cause an elderly person to have an anxiety disorder because of his health. Anxiety disorders can affect or worsen the patient's health, and anxiety can stimulate the heart rate and blood pressure. Uncontrolled blood pressure can cause symptoms to progress to organs such as the brain as strokes, as well as coronary heart disease and hypertrophy. The purpose of study: To determine the effect of murottal Al-Qur'an therapy on changes in anxiety in elderly people with hypertension in the Kalikotes Health Center working area. Research methods: The type of research used in this research is quantitative pre-experimental design research with the one group pretest-posttest design method. The sample for this study was elderly people with hypertension with a total sample of 43 respondents. The sampling technique uses purposive sampling. The instrument used was the Zung Self Rating Anxiety (ZRAS) questionnaire. Data analysis using Paired T-Test. Research results: The results of the data normality test, the data distribution in this study is normally distributed, so the correlation test used is the Paired T-Test with ap value of 0.000 (p<0.05). This means that there is a significant reduction in respondents' anxiety scores. Conclusion: There is a strong influence between the implementation of murottal Al-Qur'an therapy on anxiety in elderly people with hypertension in the Kalikotes Health Center working area.